2020
DOI: 10.3389/fcimb.2020.00118
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore-Based Virtual Screening Toward the Discovery of Novel Anti-echinococcal Compounds

Abstract: Echinococcosis is a serious helminthic zoonosis with a great impact on human health and livestock husbandry. However, the clinically used drugs (benzimidazoles) have a low cure rate, so alternative drugs are urgently needed. Currently, drug screenings for echinococcosis are mainly phenotype-based, and the efficiency of identifying active compounds is very low. With a pharmacophore model generated from the structures of active amino alcohols, we performed a virtual screening to discover novel compounds with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…), which was believed to show similar behavior. LBVS techniques that consist of substructure mining and fingerprint searches are faster than SBVS techniques (e.g., molecular docking) [22][23][24]. The benefit of combining docking primarily based digital screening with pharmacophore-primarily based digital screening is that the database of ligands can be pre-filtered by using a pharmacophore query, before assessment using docking simulations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…), which was believed to show similar behavior. LBVS techniques that consist of substructure mining and fingerprint searches are faster than SBVS techniques (e.g., molecular docking) [22][23][24]. The benefit of combining docking primarily based digital screening with pharmacophore-primarily based digital screening is that the database of ligands can be pre-filtered by using a pharmacophore query, before assessment using docking simulations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, poor understanding of drug modes of action limits target-based drug screening and design in related studies. Recently, we focused on a series of amino alcohols (Liu et al, 2018;Liu et al, 2020) because MEF, which is used for the treatment of malaria and schistosomiasis, has recently been reported to be effective against Echinococcus spp. (Kuster et al, 2011;Liu et al, 2015;Rufener et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we reported a series of amino alcohols with potential effects on Echinococcus spp. (Liu et al, 2018;Liu et al, 2020). To predict the drug targets of these compounds, idTarget, a web server for inverse docking, was used in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Our strategy was analogous to building 3D Quantitative Structure Activity Relationship (QSAR) models in drug discovery. 17,36 By aligning low energy conformations of the tested substrates, then using their field properties to generate similarity scores and compare those to their reactivity in the NADH consumption assay, we aimed to generate a pharmacophore-based screening tool which could return an assessment of the likely reactivity of a substrate molecule naïve of the active site sequence. We adopted a pragmatic approach to the development of this tool, focussing on the key information needed by a prospecting synthetic chemist asking the question "will this substrate likely be reduced by (S)-ADH?…”
Section: Confidence In Biocatalysis As a Go-to Methodsmentioning
confidence: 99%
“…However, expanding the application of biocatalysis throughout drug discovery is timely, [17][18][19] as there is an increasing appreciation of the importance of 3D character and chirality in medicinal chemistry design, 20,21 with biocatalytic technologies becoming increasingly sophisticated. 2,13,[22][23][24][25][26] Such methods could provide ready access to enantioenriched building blocks.…”
Section: Introductionmentioning
confidence: 99%